Cyber Victimology and Legal Gaps in Southeast Asia - Fernando, Zico Junius; Widyawati, Anis; Rinaldi, Kasmanto (Universitas Negeri Semarang, 2025)
Cybercrime is escalating in Southeast Asia alongside rapid digital growth, yet the region still lacks a unified legal and victim-centered approach. While most studies focus on perpetrators and cybersecurity, this research addresses a critical gap by exploring Cyber Victimology as a framework to understand and strengthen victim protection in ASEAN countries. Using a normative legal method with comparative and conceptual approaches, this study examines legal disparities, weak law enforcement, limited victim support, and low digital literacy, particularly among children and the elderly. Findings show that ASEAN lacks harmonized regulations, adequate cyber policing, and psychological-legal support infrastructure. For instance, Singapore’s robust Personal Data Protection Act contrasts with minimal protection in Cambodia and Laos. The study proposes concrete policy responses, including regional legal harmonization modeled on the Budapest Convention and the GDPR, enhanced law enforcement capacity, national crisis centers, and targeted digital literacy programs. Integrating Cyber Victimology into policy will help ASEAN establish a more inclusive, victim-responsive digital governance system.